Motor coordination: quality of elderly movement - Charal, Claudiana Marcela Siste (2022)
Aging is an irreversible event in the individual, in which there are significant losses that influence the quality of life. Motor coordination is one of the losses that brings dependence and harms the life of the elderly. Therefore, this study is a bibliographic review based on articles and books, with the objective of defining, classifying motor coordination and pointing out the benefits of physical activity in the elderly. For the same, the themes were used as descriptors: elderly, motor coordination, physical exercises and movement. Initially, a search was carried out in the Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO), Google Scholar and periodical books databases. This review classified and pointed out the importance of motor coordination for the elderly and the impact of physical activity on them. Therefore, it is concluded in this work that the motor coordination starts from birth and goes through the years, and must be stimulated so that there is a harmony in the movements, the practice of physical activity helps in the improvement of coordination, and especially the elderly need to improve quality of life and autonomy in aging.